An ESR1-related gene signature identifies head and neck squamous cell carcinoma with imputed susceptibility to endocrine therapy - Almouhanna, Firas; Heß, Jochen (International journal of molecular sciences, 2024)
Head and neck squamous cell carcinoma (HNSCC) is associated with high morbidity and mortality. New personalized treatment strategies represent an unmet medical need to improve the overall survival and the quality of life of patients, which are often limited by the toxicity of established multimodal treatment protocols. Several studies have reported an increased expression of the estrogen receptor 1 (ESR1) in HNSCC, but its potential role in the disease outcome of these tumors remains elusive. Using an integrative analysis of multiomics and clinical data from The Cancer Genome Atlas (TCGA)-HNSC, we established a prognostic risk model based on an ESR1-related 25-gene set. The prognostic value was confirmed in an independent cohort of HNSCC and other solid tumors from TCGA. Finally, we performed in silico drug sensitivity modeling to explore potential vulnerabilities for both risk groups. This approach predicted a higher sensitivity for HNSCC, with prominent ESR1 pathway activity under treatment with specific estrogen receptor modulators. In conclusion, our data confirm the involvement of ESR1-related pathway activity in the progression of a defined subset of HNSCC, provide compelling evidence that these tumors share a specific vulnerability to endocrine therapy, and pave the way for preclinical studies and clinical trials to demonstrate the efficacy of this new therapeutic option.